An Assessment of Urinary Biomarkers in a Series of Declined Human Kidneys Measured During Ex Vivo Normothermic Kidney Perfusion. Issue 9 (September 2017) - Hosgood, Sarah A.; Nicholson, Michael L.
Abstract : Background: The measurement of urinary biomarkers during ex vivo normothermic kidney perfusion (EVKP) may aid in the assessment of a kidney prior to transplantation. This study measured levels of neutrophil gelatinase-associated lipocalin (NGAL), kidney injury molecule-1 (KIM-1) and endothelin-1 (ET-1) during EVKP in a series of discarded human kidneys. Methods: Fifty-six kidneys from deceased donors were recruited into the study. Each kidney underwent 60 minutes of EVKP and was scored based on the macroscopic appearance, renal blood flow and urine output. The scores ranged from 1 (least injury) to 5 (most severe). Levels of oxygen consumption, extraction, creatinine fall and fractional excretion of sodium were measured during perfusion. Urinary levels of NGAL, KIM-1, and ET-1 were measured after EVKP. Results: Thirty-eight kidneys had an EVKP score of 1 or 2, 8 a score of 3 and 10 a score of 4 or 5. During EVKP lower levels of oxygen consumption, higher oxygen extraction, a lower decrement of serum creatinine, and higher levels of NGAL and ET-1 were associated with a higher EVKP score ( P < 0.05). These parameters were also associated with a raised creatinine level in the donor before organ retrieval. Levels of KIM-1 were not associated with the perfusion parameters ( P = 0.649) or renal function in the donor ( R 2 = 0.02458: P = 0.271). Conclusions: The measurement of urinary biomarkers, particularly NGAL in combination with functional perfusion parameters and the EVKP score provides an informative measure of kidney quality which may aid the decision to transplant the kidney. Abstract : This study of the measurement of neutrophil gelatinase-associated lipocalin (NGAL), kidney injury molecule-1 (KIM-1) and endothelin-1 (ET-1) during ex-vivo normothermic kidney perfusion of 56 discarded kidneys shows that NGAL with functional perfusion parameters and the EVKP score could assist in determining which kidneys are usable.